2016
DOI: 10.1007/s10695-016-0245-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a vasa homolog in the brown-marbled grouper (Epinephelus fuscoguttatus) and its expression in gonad and germ cells during larval development

Abstract: The vasa gene is specifically expressed in the germ cell lineage, and its expression has been used to study germline development in many organisms, including fishes. In this study, we cloned and characterized vasa as Efu-vasa in the brown-marbled grouper (Epinephelus fuscoguttatus). Efu-vasa contained predicted regions that shared consensus motifs with the vasa family in teleosts, including arginine- and glycine-rich repeats, ATPase motifs, and a DEAD box. Phylogenetic-tree construction using various DEAD-box … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
3
10
0
Order By: Relevance
“…Vasa, a germ cell marker [22], is required for proper germ cells development. Its expression levels were decreased gradually with the progress of spermatogenesis, which is consistent with the expression pattern of vasa in the male germ cells of gibel carp [22] and brown-marbled grouper [18]. As an oocyte-specific marker [19,23], slbp2 was used to distinguish the female germ cell and male germ cell.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Vasa, a germ cell marker [22], is required for proper germ cells development. Its expression levels were decreased gradually with the progress of spermatogenesis, which is consistent with the expression pattern of vasa in the male germ cells of gibel carp [22] and brown-marbled grouper [18]. As an oocyte-specific marker [19,23], slbp2 was used to distinguish the female germ cell and male germ cell.…”
Section: Discussionsupporting
confidence: 71%
“…Its expression was detected in all four types of male germ cells at similar levels. Vasa is a germ cell marker [18] whose expression was also found in the four cell types. Slbp2 was specifically expressed in the oocyte of orangespotted grouper [19], and no expression was detected in any male germ cells except for in the positive control (the gonad containing primary-growth stage oocytes).…”
Section: Validation Of the Sample Qualitymentioning
confidence: 99%
“…Then the PGCs along with stromal cells started to migrate from the anus prior to 5 dpf and PGC proliferation in the gonadal anlagen was initiated at 7–10 dpf and the number of PGCs became double at 30 dpf (22 ± 3·2 cells), compared to that at 1 dpf (11 ± 2·1 cells) (Kobayashi et al, ). In the brown‐marbled grouper Epinephelus fuscoguttatus (Forsskål 1775), the PGCs' proliferation seems to be slower than that of other fish, it was observed that the PGC migration occurred from 9 dpf to 15 dpf, the PGC arrival at the destination and the genital ridge formation phase were from 15 to 27 dpf, then the PGC proliferation phase was observed after 32 dpf (Boonanuntanasarn et al, ). Similarly, to develop techniques for A. sapidissima breeding and germ‐cells manipulation, the migration of PGCs was examined in A. sapidissima embryos at tail‐bud and pre‐hatching stages using morphometric analysis and WISH using the ASvas mRNA probe.…”
Section: Discussionmentioning
confidence: 99%
“…The whole process of LCM must produce sufficient amount of RNA with high quality to ensure the reliability of the transcriptome results. In this study, we modified a previous protocol [18]. As an oocyte-specific marker [19,23] [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Its expression was detected in all four types of male germ cells at similar levels. Vasa is a germ cell marker [18] whose expression was also found in the four cell types. Slbp2 was specifically expressed in the oocyte of orange-spotted grouper [19], and no expression was detected in any male germ cells except for in the positive control (the gonad containing primary-growth stage oocytes).…”
Section: Validation Of the Sample Qualitymentioning
confidence: 99%